Upaya Meningkatkan Hasil Belajar Bahasa Indonesia melalui Penggunaan Media Gambar Siswa Kelas VIII.H SMP Negeri 12 Mataram - Mukasri, Mukasri (TSAQOFAH, 2022)
This study aims: to find out the use of media images in learning Indonesian in class VIII.H students at SMP Negeri 12 Mataram Odd Semester in the Academic Year 2021/2022. And to find out the increase in Indonesian learning outcomes through the use of media pictures of class VIII.H students of SMP Negeri 12 Mataram Odd Semester 2021/2022 Academic Year. This research was designed using Classroom Action Research. The subjects in this study were class VIII.H students of SMP Negeri 12 Mataram, totaling 31 people, consisting of 15 female students and 16 male students. While the research procedure goes through the stages of Planning, Action Implementation, Observation, and reflection. The results showed that the results of learning Indonesian for class VIII.H students of SMP Negeri 12 Mataram in the 2021/2022 academic year, using media images could be improved with the final result of the study being the class average before the action of 69.06 or classical completeness of 61.29 %, to 73.68 or 74.19% classical completeness in cycle I, increased to an average of 74.84 or 77.55% in cycle II and increased to an average test of 80.45 or 100% in cycle III. From the results of student observations it was shown that there was an increase in student activity in cycle I obtained a score of 17 or 60.70% to 20 or 71.43% in cycle II and 24 or 85.17 in cycle III. The increase in student activity in learning Indonesian was supported by the increase in teacher activity in maintaining and improving the learning atmosphere using media images, this can be seen from the observations of teacher activities where in cycle I a score of 22 or 61.10% was obtained, becoming 26 or 72, 23% in cycle II and increased to 33 or 86.12% in cycle III.